Dynamics of a Discrete Host-Parasitoid System with Stocking - Sophia R.-J. Jang (Discrete Dynamics in Nature and Society)
Motivated by the biological control of pests, we present discrete-time models of host-parasitoid interactions to study the effects of external stocking upon the systems. It is assumed that density dependence of the hosts occurs first followed by parasitism. We prove that the constant stocking can eliminate the pest population if the stocking is sufficiently large. Furthermore, stocking can simplify the dynamics of the interaction by stabilizing the coexisting steady state.